Analisis Efektivitas dan Efisiensi Realisasi Anggaran Belanja pada Dinas Perindustrian, Perdagangan, Energi dan Sumber Daya Mineral Kabupaten Garut - Tiara Nurul Hidayat; Etti Ernita Sembiring; Darya Setia Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to analyze the effectiveness and efficiency of budget realization at the Department of Industry, Trade, Energy and Mineral Resources in the 2018-2020 budget. This research is a quantitative research. data sources are secondary data and primary data in the form of a Budget Realization Report (LRA) and also in the form of interviews. Data analysis used by calculating the ratio of effectiveness and efficiency and also processing interview data. The results of the study show the criteria for the effectiveness of the implementation of the budget in 2018 with effective criteria, in 2019 with ineffective criteria and in 2020 the criteria are less effective. Efficiency Criteria The implementation of the budget in 2018 and 2019 shows that it has been efficient and in 2020 it is very efficient.